Validation of an analytical method using an anion-exchange monolithic column for the assessment of supercoiled plasmid DNA - Mota, Élia Marília da Fonte (2012)
The demand of high-purity supercoiled (sc) plasmid DNA (pDNA) to be applied as a vector for new therapeutic strategies, such as gene therapy or DNA vaccination has increased in the last years. Thus, it is necessary the implementation of an analytical technique suitable to control the quality of the sc pDNA as a pharmaceutical product, during the manufacturing process. The present study describes a new methodology to quantify and monitor the purity of sc pDNA, using a monolithic column based on anion-exchange chromatography. This analytical method with UV detection allows the separation of the plasmid isoforms by using a NaCl stepwise gradient. The selectivity, linearity, accuracy, reproducibility and repeatability of the method have been evaluated, and the lower quantification and detection limits were also established. The validation was performed according to the guidelines, being demonstrated that the method is precise and accurate for a sc plasmid concentration up to 200 µg/mL. The main advance achieved by using this monolithic method is the possibility to quantify the sc plasmid in a sample containing other plasmid topologies, in a 4 minutes experiment. This column also permits the assessment of the sc pDNA present in more complex samples, allowing the control of pDNA throughout the bioprocess. Thus, these findings strengthen the possibility of using this monolithic column associated with a powerful analytical method to control the downstream process of sc pDNA for therapeutic applications.